Oncoplastic breast‐conserving therapy and intraoperative radiotherapy for management of carcinoma in situ of the breast: A single‐center experience. Issue 12 (6th December 2020) - Crown, Angelena; Carlson, Elizabeth; Rocha, Flavio G.; Grumley, Janie W.
Abstract: Intraoperative radiation therapy (IORT) has been shown to reduce local recurrence rates among women with early‐stage invasive ductal carcinoma, but data regarding its use among women with in situ carcinoma are limited. In this single‐institution study, 50 women with in situ carcinoma were treated with oncoplastic breast‐conserving surgery (OPS) and single‐dose IORT. All 50 patients had "no tumor on ink, " but 9 (16%) had margins < 2 mm and required additional therapy. No local recurrences were observed after a median follow‐up of 46 months. Single‐dose IORT is an efficacious treatment for well‐selected patients with DCIS.